Ethnobotanical Study on Medicinal Plants in Sesaot Forest, Narmada,West Lombok, Indonesia - Slamet Mardiyanto Rahayu; Arista Suci Andini (Biosaintifika: Journal of Biology & Biology Education, 2019)
Indonesia is one of the largest mega biodiversity countries in the world that is rich in biological resources. Plants can be an alternative in treating diseases by Indonesian people such as around the Sesaot Forest, the Buwun Sejati Village. This study aimed to determine the types of plants in Sesaot Forest which were used as medicine by the people of Buwun Sejati Village, Narmada District, West Lombok Regency. This research was conducted by interview method and field survey. Data analysis was carried out descriptively. Based on the research, there were 87 species included in 42 families used as medicine by the community of Buwun Sejati Village. The Zingiberaceae family was a plant family that was most widely used as a traditional medicine ingredient. There were 30 types of diseases treated using Sesaot Forest plants by the community of Buwun Sejati Village. Leaves were of the most common part of plant used as raw material for traditional medicine by the people of Buwun Sejati Village, Narmada District, West Lombok Regency. The advantages of traditional medicines include its widespread accessibility and relative low prices. Therefore, this data obtained from this study is necessary to inventory the kind of medicinal plants and their utilization by the community, so that, the traditional knowledge of the medicinal plants can be documented and preserved.